2019
DOI: 10.21203/rs.2.10177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific impact of patterns of imageable tumor growth on survival of primary glioblastoma patients

Abstract: Background: Sex is recognized as a significant determinant of outcome among glioblastoma patients, but the relative prognostic importance of glioblastoma features has not been thoroughly explored for sex differences. Methods: Combining multi-modal MR images, biomathematical models, and patient clinical information, this investigation assesses which pretreatment variables have a sex-specific impact on the survival of glioblastoma patients (299 males and 195 females). Results: Among males, tumor (T1Gd) radius wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This could reduce the computational expense and potentially lead to more accurate predictions. Finally, recent works [18,44] have noted differences in gliomas based on patient sex and have called for the inclusion of this information in analysis. For our work, it would be interesting to observe the differences in parameter predictions for male and female patients, though this would require a much larger dataset than we have used in order to be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…This could reduce the computational expense and potentially lead to more accurate predictions. Finally, recent works [18,44] have noted differences in gliomas based on patient sex and have called for the inclusion of this information in analysis. For our work, it would be interesting to observe the differences in parameter predictions for male and female patients, though this would require a much larger dataset than we have used in order to be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, medical imaging provides non-invasive, serial observations of the spatiotemporal variations in the physical state of the patient, which can be employed as the observational data of a patient's digital twin. We [11,29,[43][44][45][46] and others [47][48][49][50][51] have demonstrated that mathematical models can be initialized and personalized by medical imaging data collected from patients. Once personalized, the image-guided mathematical model parameters serve as a digital representation of that patient's tumor where treatment can be optimized and response can be forecasted.…”
Section: Integrating Quantitative Imaging and Mechanism-based Mathema...mentioning
confidence: 99%